Penerapan Efektivitas Pengawasan Hukum terhadap Manajemen Kepegawaian Daerah dalam Era Otonomi : Tantangan, Solusi, dan Implikasi terhadap Akuntabilitas Pemerintahan - Berlian Evi Yenni Pakpahan; Ismaidar Ismaidar; Suci Ramadani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study discusses the implementation of the effectiveness of legal oversight of regional personnel management in the era of regional autonomy. Regional autonomy grants broad authority to regional governments to regulate and manage public interests, including in the management of state civil servants (ASN). However, this authority often gives rise to problems, such as nepotism, politically motivated job transfers, and weak accountability in personnel management. Legal oversight is an important instrument to ensure that all personnel policies and practices are implemented in accordance with the principles of legality, professionalism, and accountability. The research method used is normative legal research with a statutory, conceptual, and case approach, as well as qualitative analysis of regulations and personnel oversight practices. The results of the study indicate that the effectiveness of legal oversight is greatly influenced by the consistency of regulatory implementation, the strength of supervisory institutions such as the State Civil Service Commission (KASN) and the State Civil Service Agency (BKN), and the legal culture of regional apparatus. Strict enforcement of sanctions against violations also plays an important role in maintaining the integrity of the merit system. The conclusion of this study confirms that effective legal oversight can prevent abuse of authority, strengthen the professionalism of civil servants (ASN), and support the achievement of regional autonomy goals, namely improving the quality of public services and public welfare. Therefore, strengthening regulations, supervisory institutions, and internalizing the values ​​of good governance are necessary to realize transparent, accountable, and integrity-based regional personnel management.